Nonalcoholic fatty liver disease induced by noncanonical Wnt and its rescue by Wnt3a. Issue 8 (10th November 2017) - Wang, Shuxia; Song, Kangxing; Srivastava, Roshni; Dong, Chao; Go, Gwang‐Woong; Li, Na; Iwakiri, Yasuko; Mani, Arya
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease, which begins with isolated steatosis and advances to nonalcoholic steatohepatitis (NASH), steatofibrosis, and cirrhosis. The pathways involved in disease progression are not understood. Loss‐of‐function mutations in Wnt coreceptor LDL receptor‐related protein 6 (LRP6) underlie early‐onset atherosclerosis, metabolic risk factors, and NAFLD in humans by unknown mechanisms. We generated mice with the human disease‐associated LRP6 R611C mutation and phenotypically characterized their liver. Homozygote LRP6 R611C (LRP6 mut/mut ) mice exhibited both steatohepatitis and steatofibrosis. These traits were associated with increased activity of the noncanonical Wnt/Ras homolog family member A, Rho‐associated protein kinase 2, and PKC‐α/‐μ pathways. Accordingly, there was increased TGF‐β1 activity, coupled with enhanced expression of smooth muscle α‐actin and vimentin that colocalized with albumin in LRP6 mut/mut mouse liver. LRP6 knockdown reprogramed HepG2 cells to express both these markers, linking impaired Wnt signaling with hepatocyte transdifferentiation. The causal link between altered Wnt signaling and NASH was established by normalization of the disease pathways and rescue of the liver traits by Wnt3a administration to LRP6 mut/mut mice. Thus, this study identifies diverse disease pathways that underlie a spectrum of NASH‐related liver diseases and are linked by a single human genetic variant. LRP6 and noncanonical Wnt pathways are important potential therapeutic targets against NASH.—Wang, S., Song, K., Srivastava, R., Dong, C., Go, G.‐W., Li, N., Iwakiri, Y., Mani, A. Nonalcoholic fatty liver disease induced by noncanonical Wnt and its rescue by Wnt3a. FASEB J. 29, 3436‐3445 (2015). www.fasebj.org